Conversion of haloacid disinfection byproducts to amino acids via ammonolysis. (June 2019) - Li, Wanxin; Li, Yu; Zhang, Xiangru; Han, Jiarui; Zhu, Xiaohu; Choi, Ka Chun; Jiang, Jingyi
Abstract: Haloacetic acids (HAAs) are the major disinfection byproducts (DBPs) that are formed during chlorination of drinking water. In this paper, the conversion of HAAs to amino acids (e.g., glycine) via ammonolysis was studied. First, a new and sensitive method for detecting glycine was developed by setting selected ion recording m/z 76 in positive electrospray ionization mass spectrometry coupled with ultra performance liquid chromatography. Second, among the mono-HAAs under the same test conditions, iodoacetic acid (49.3%) showed a considerably higher conversion to glycine during ammonolysis than chloroacetic acid (4.2%) and bromoacetic acid (27.7%). The conversion of iodoacetic acid to glycine increased with increasing temperature, increasing reaction time, or decreasing the ratio of (NH4 )2 CO3 to NH3 ·H2 O in the aminating agent. Hydrolysis of iodoacetic acid to glycolic acid was also observed during ammonolysis, and it accounted for at most 50% of the iodoacetic acid conversion. The conversion to amino acids and the hydrolysis were the two major pathways during ammonolysis of HAAs. Third, compared with the iodoacetic acid sample and the simulated tap water sample without ammonolysis, the developmental toxicity of the corresponding samples with ammonolysis decreased by up to 10.4% and 32.1%, respectively. The ammonolysis was thus demonstrated to be a detoxification process for both individual HAAs and DBP mixture in chlorinated tap water. In practice, the ammonolysis of haloacid DBPs in tap water may be realized by simply adding an appropriate amount of an aminating agent during cooking. Graphical abstract: Image 1 Highlights: A new and sensitive method for measuring glycine was developed. Mono-HAAs were converted to glycine by ammonolysis. Factors affecting the ammonolysis reaction were investigated. Ammonolysis reduced the toxicity of chlorinated tap water.